2010
DOI: 10.1016/j.fitote.2009.08.003
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatographic analysis and anticancer potential of Oplopanax horridus: Comparison of stem and berry extracts

Abstract: Oplopanax horridus or devil’s club is a herbal medicine distributed in North America. The constituents and pharmacological activities of O. horridus (OPH) are largely unknown. In this study, we assayed OPH stem and berry extracts using high performance liquid chromatography (HPLC). The anticancer potentials of extracts on different human cancer cell lines (SW-480, HCT-116, HT-29, MCF-7 and NSCLC) were determined by MTS method. The effect of stem extract on cancer cell cycle, expression of cyclin A, and apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…2, the whole extract of dried roots at concentrations of 0.1 and 0.2 mg/mL showed obvious anti-proliferative effect on the HT-29 cells, which were inhibited at 29.8% and 56.5%, respectively. The anti-cancer effect of the Devil's club extract against the HT-29 cells was also reported in another study, which indicated the stem of the Devil's club could inhibit 52% cell growth at the extract concentration of 0.25 mg/mL, and 84% at 0.5 mg/ml (Wang, Aung, Mehendale, Shoyama, & Yuan, 2010). Such differences in the anti-cancer activity of the Devil's club extract might result from the difference of chemical profiles between the root and stem, as well as the hydrolysis processing in sample preparation.…”
Section: Anti-cancer (Cell Proliferation Assay)supporting
confidence: 57%
“…2, the whole extract of dried roots at concentrations of 0.1 and 0.2 mg/mL showed obvious anti-proliferative effect on the HT-29 cells, which were inhibited at 29.8% and 56.5%, respectively. The anti-cancer effect of the Devil's club extract against the HT-29 cells was also reported in another study, which indicated the stem of the Devil's club could inhibit 52% cell growth at the extract concentration of 0.25 mg/mL, and 84% at 0.5 mg/ml (Wang, Aung, Mehendale, Shoyama, & Yuan, 2010). Such differences in the anti-cancer activity of the Devil's club extract might result from the difference of chemical profiles between the root and stem, as well as the hydrolysis processing in sample preparation.…”
Section: Anti-cancer (Cell Proliferation Assay)supporting
confidence: 57%
“…Miq. (Araliaceae) effectively inhibit the proliferation of breast cancer cells via induction of cell cycle arrest (Wang et al, 2010). The extracts of Citrus grandis Osbeck (Rutaceae) and Onosma paniculatum Bur.…”
Section: Discussionmentioning
confidence: 99%
“…O. elatus is distributed throughout eastern Asia, including northeast China, Korea and the far east of Russia. Another species from this genus, O. japonicus , is distributed throughout Japan [5]. …”
Section: Botanical Studiesmentioning
confidence: 99%
“…The plant is a member of the family Araliaceae, the same family as more familiar plants such as American ginseng and is therefore occasionally referred to as “Alaskan ginseng” or “Pacific ginseng,” although they are in different genera [2-4]. There are three different species within Oplopanax , which include O. horridus, O. japonicus and O. elatus [5]. O. japonicus and O. elatus are distributed throughout Japan and eastern Asia, respectively [5], and there are beyond the scope of this article.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation